Comparative Analysis of the Antihypertensive Effects of Red Palm Oil and Pumpkin Seed Oil in Nω-Nitro-L-arginine Methyl Ester-Induced Hypertensive Rats - Adeniran, Francis Temitope; Oladapo, Olulola Olutoyin (Journal of Medical Health Research and Psychiatry, 2025)
Background: Hypertension is a prevalent cardiovascular disease with global health implications. Dietary interventions with local Nigerian food items offer promise in hypertension management, but the comparative effects of Red Palm Oil (RPO) and Pumpkin Seed Oil (PSO) are underexplored. This study investigated the effects of RPO and PSO supplementation on hypertension in male Wistar rats, focusing on onset of action and effectiveness. Methods: Thirty-six male adult Wistar rats were divided into six groups: Control, RPO without hypertension induction, PSO without hypertension induction, RPO after hypertension induction, PSO after hypertension induction and hypertension induction without supplementation. Hypertension was induced using Nω-Nitro-L-arginine methyl ester over three weeks, followed by five weeks of intervention. Blood pressure and weight were monitored weekly. RPO and PSO supplementation in normotensive rats showed no significant body weight changes. Results: By week 4, hypertensive groups showed a significant weight reduction compared to normotensive groups. Both RPO and PSO reduced systolic blood pressure compared to hypertensive controls (162.17 ± 2.3 vs. 136.40 ± 0.75, 134.20 ± 1.53 mmHg). RPO showed earlier efficacy by week 5, while PSO's effect was significant by week 7. Both oils reduced diastolic blood pressure by week 6 (147.00 ± 9.04 vs. 96.00 ± 4.53, 93.00 ± 3.99 mmHg) and lowered mean arterial pressure (145.00 ± 1.34 vs. 109.00 ± 2.49, 115.67 ± 1.48 mmHg). Discussion and Conclusion: Supplementation with Red Palm Oil (RPO) or Pumpkin Seed Oil (PSO) did not significantly affect heart weight index compared to the normal control group. Additionally, there were no significant differences between RPO and PSO when compared with the control and when compared within each condition. However, hypertension induction led to a significant change in heart weight index compared to the normal control group.